EFEKTIVITAS MODEL PROBLEM BASED LEARNING METODE TUTOR SEBAYA BERBANTUAN CARD PROBLEM TERHADAP HASIL BELAJAR MATEMATIKA - Amaliyatul Indah; Susanto Susanto; Abi Suwito; Sunardi Sunardi; Didik Sugeng Pambudi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Learning mathematics is frequently regarded as difficult by students, resulting in a lack of problem-solving ability. This problem occurred at SMPN 8 Jember, where, based on the results of observations, grade VII students have low problem-solving skills due to the conventional learning model used. If the problem is not addressed immediately, it is feared that it will continue with the next generation of students. This study aims to determine the effectiveness of PBL model of the peer tutor method assisted by card problems on mathematics learning outcomes in seventh-grade junior high school students with quadrilateral material. This research includes a quasi-experimental design. The data collection technique uses pretest and posttest tests to be tested with the paired samples T test and regression test (ANOVA) on the SPSS application. The results of the paired samples T test in the experimental class gave a sig value of 0.000, while in the control class it was 0.003. The sig value for the regression test for the experimental class is 0.014, while the sig value for the control class is 0.033. These results show that the PBL model of the peer tutor method assisted by card problems is more effective and influential than the PBL model of the peer tutor method to improve student mathematics learning outcomes. The study concludes that incorporating card problem learning media into the PBL model of the peer tutor method produces effective results in terms of quadrilateral material mathematics learning outcomes.